PENERAPAN MODIFIKASI PERMAINAN MENGGUNAKAN MEDIA CONE UNTUK MENINGKATKAN HASIL BELAJAR GERAK LOKOMOTOR SISWA SD MIDU GEDONGAN WARU - Moh. Yusroni; Brahmana Rangga Prastyana; Gatot Margisal Utomo (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2022)
The results of observations that have been made to third grade students at SD Ngingas Minu Waru Midu Gedangan Sidoarjo, there are still many students who are less than optimal in practicing locomotor movements. This can be seen in the results of the assessment of the locomotor range of motion. The purpose of the action research is the application of game modifications using cone media in order to improve locomotor learning outcomes for students at SD Ngingas Minu Waru Midu Gedangan Sidoarjo. The method used in this research is to use a classroom action research design with 2 cycles. The population and sample of the study were 25 grade III students. The research was carried out in four stages, namely planning, implementation, observation, and reflection. The results of the study were analyzed using percentages. The results showed that there was an increase in locomotor movement learning outcomes after applying the game modification with cone media. The increase in learning outcomes occurred in cycle 2 with a percentage of 88% entering the Completed criteria. Based on the results of these studies, it can be concluded that the application of game modifications with cone media can improve locomotor learning outcomes for third grade students of SD Ngingas Minu Waru Midu Gedangan Sidoarjo.